Competitive Absorption and Inefficient Exciton Harvesting: Lessons Learned from Bulk Heterojunction Organic Photovoltaics Utilizing the Polymer Acceptor P(NDI2OD‐T2). (2nd September 2014) - Li, Zhi; Lin, Jason D. A.; Phan, Hung; Sharenko, Alexander; Proctor, Christopher M.; Zalar, Peter; Chen, Zhihua; Facchetti, Antonio; Nguyen, Thuc‐Quyen
<x xml:space="preserve">Abstract</x> Organic solar cells utilizing the small molecule donor 7, 7′‐(4, 4‐bis(2‐ethylhexyl)‐4H‐silolo[3, 2‐b:4, 5‐b′]dithiophene‐2, 6‐diyl)bis(6‐fluoro‐4‐(5′‐hexyl‐[2, 2′‐bithiophen]‐5‐yl)benzo[c][1, 2, 5] thiadiazole) (p‐DTS(FBTTh2)2 and the polymer acceptor poly[N, N′‐bis(2‐octyldodecyl)‐1, 4, 5, 8‐naphthalenedicarboximide‐2, 6‐diyl]‐alt‐5, 5′‐(2, 2′‐bithiophene)(P(NDI2OD‐T2)) are investigated and a power conversion efficiency of 2.1% is achieved. By systematic study of bulk heterojunction (BHJ) organic photovoltaic (OPV) quantum efficiency, film morphology, charge transport and extraction and exciton diffusion, the loss processes in this blend is revealed compared to the blend of [6, 6]‐phenyl‐C71‐butyric acid methyl ester (PC71BM) and the same donor. An exciton diffussion study using Förster resonant energy transfer (FRET) shows the upper limit of the P(NDI2OD‐T2) exciton diffusion length to be only 1.1 nm. The extremely low exciton diffusion length of P(NDI2OD‐T2), in combination with the overlap in donor and acceptor absorption, is then found to significantly limit device performance. These results suggest that BHJ OPV devices utilizing P(NDI2OD‐T2) as an acceptor material will likely be limited by its low exciton diffusion length compared to devices utilizing functionalized fullerene acceptors, especially when P(NDI2OD‐T2) significantly competes with the donor molecule for photon absorption.